Maternal Cardiac Arrest: A Practical and Comprehensive Review - Farida M. Jeejeebhoy; Laurie J. Morrison (Emergency Medicine International)
Cardiac arrest during pregnancy is a dedicated chapter in the American Heart Association Guidelines for Cardiopulmonary Resuscitation and Emergency Cardiovascular Care; however, a robust maternal cardiac arrest knowledge translation strategy and emergency response plan is not usually the focus of institutional emergency preparedness programs. Although maternal cardiac arrest is rare, the emergency department is a high-risk area for receiving pregnant women in either prearrest or full cardiac arrest. It is imperative that institutions review and update emergency response plans for a maternal arrest. This review highlights the most recent science, guidelines, and recommended implementation strategies related to a maternal arrest. The aim of this paper is to increase the understanding of the important physiological differences of, and management strategies for, a maternal cardiac arrest, as well as provide institutions with the most up-to-date literature on which they can build emergency preparedness programs for a maternal arrest.